The costs of mitigating carbon emissions in China: findings from China MARKAL-MACRO modeling - Chen, Wenying (Energy policy, 2005)
In this paper MARKAL-MACRO, an integrated energy-environment-economy model, is used to generate China’s reference scenario for future energy development and carbon emission through the year 2050. The results show that with great efforts on structure adjustment, energy efficiency improvement and energy substitution, China’s primary energy consumption is expected to be 4818 Mtce and carbon emission 2394 MtC by 2050 with annual decrease rate of 3% for the carbon intensity per GDP during the period 2000–2050. On the basis of this reference scenario, China’s marginal abatement cost curves of carbon for the year 2010, 2020 and 2030 are derived from the model, and the impacts of carbon emission abatement on GDP are also simulated. The results are compared with those from other sources. The research shows that the marginal abatement costs vary from 12US$/tC to 216US$/tC and the rates of GDP losses relative to reference range from 0.1% to 2.54% for the reduction rates between 5% and 45%. Both the marginal abatement costs and the rates of GDP losses further enlarge on condition that the maximum capacity of nuclear power is constrained to 240 GW or 160 GW by 2050. The paper concludes that China's costs of carbon abatement is rather high in case of carbon emissions are further cut beyond the reference scenario, and China's carbon abatement room is limited due to her coal-dominant energy resource characteristic. As economic development still remains the priority and per capita income as well as per capita carbon emission are far below the world average, it will be more realistic for China to make continuous contributions to combating global climate change by implementing sustainable development strategy domestically and playing an active role in the international carbon mitigation cooperation mechanisms rather than accepting a carbon emission ceiling.